Chinese Overseas Finance in Renewable Energy in Argentina and Brazil: Implications for the Energy Transition - Tatiana Gélvez Rubio; Juliana González Jáuregui (Journal of Current Chinese Affairs, 2022)
China began to accelerate the energy transition in the last decade as a strategy for rebalancing its economy and becoming a more influential actor in the global renewable energy market. This article explores to what extent Chinese investment and financing in renewable energy projects in Argentina and Brazil promote these countries' energy transition strategies and sustainable development more broadly. To approach this question, the article provides a reading of Ostrom’s postulates of the energy transition as an increasingly relevant driver of certain states’ relationships with other countries. General trajectories of Chinese investment and lending in Latin America provide a background to Chinese investment in solar and wind power projects in Argentina and Brazil. The article concludes that China’s overseas finance merges with Argentina and Brazil’s own goals regarding renewable energy deployment and discusses future challenges in the context of the COVID-19 pandemic and its aftermath.